1989
DOI: 10.1111/j.1472-765x.1989.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel radiation-resistant Deinobacter sp. isolated from irradiated pork

Abstract: A red-pigmented, radiation-resistant, Gram-negative, rod-shaped bacterium isolated from irradiated pork is described. The D,, values in buffer solution and on pork mince are 3. 45 and 5.05 kGy respectively. The strain has been identified as a Deinobacter species.The sensitivity of micro-organisms to ionizing radiation can vary with genus, species or strain. The relative sensitivity of bacteria to gamma irradiation is compared by calculating D,, values where the D,, is the dose required to inactivate 90% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
(7 reference statements)
1
12
0
Order By: Relevance
“…Species of these two genera made up 82% of the isolates recovered from the soil sample after exposure to doses of ionizing radiation of 17 kGy or more. At the highest doses (23,25, and 30 kGy), Deinococcus species accounted for more than 72% of the isolates recovered, and Geodermatophilus and Hymenobacter species accounted for 23 and 5%, respectively. Of the 126 isolates recovered and identified from the soil sample exposed to various levels of ionizing radiation in this study, 106 belonged to these three genera (Deinococcus, 60 strains; Geodermatophilus, 40 strains; and Hymenobacter, 6 strains).…”
Section: ϫ5mentioning
confidence: 99%
See 3 more Smart Citations
“…Species of these two genera made up 82% of the isolates recovered from the soil sample after exposure to doses of ionizing radiation of 17 kGy or more. At the highest doses (23,25, and 30 kGy), Deinococcus species accounted for more than 72% of the isolates recovered, and Geodermatophilus and Hymenobacter species accounted for 23 and 5%, respectively. Of the 126 isolates recovered and identified from the soil sample exposed to various levels of ionizing radiation in this study, 106 belonged to these three genera (Deinococcus, 60 strains; Geodermatophilus, 40 strains; and Hymenobacter, 6 strains).…”
Section: ϫ5mentioning
confidence: 99%
“…Of the genera containing ionizing-radiation-resistant organisms, Deinococcus and Rubrobacter show the highest levels of resistance, and all species of these genera have been shown to be either gamma radiation resistant or UV radiation resistant or both (2,6,19,20,22,47,61,62,73 (5,19,26,52,61). Other ionizing-radiationresistant bacteria have been isolated and described; these include some species of the genera Acinetobacter, Chroococcidiopsis, Hymenobacter, Kineococcus, Kocuria, and Methylobacterium (4,5,11,23,24,30,49,50,53). Hyperthermophilic euryarchaeote species of the genera Thermococcus and Pyrococcus also contain ionizing-radiation-resistant strains (15,32,33).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Several researchers have reported that some pigmented bacteria, which are rich in carotenoids have been resistant to radiation when subjected to sub-lethal and lethal doses of ionizing radiations, due to the accumulation of the radio-protective pigments in the outer membrane. [3][4][5][6] Carotenoids are the terpenoid pigments produced by a wide variety of plants and microbes, which are reported to have radio-protective property. [7] Carotenoid pigments of bacterial origin have been reported to have radio-protective and antioxidant properties, and as natural coloring agents.…”
Section: Introductionmentioning
confidence: 99%